ROLE OF PHYSICAL DEVELOPMENT PARAMETERS IN DETERMINATION OF AGE OF JUVENILES: A RESEARCH STUDY - Dabas, C B; Sharma, S K (Journal of Forensic Medicine and Toxicology, 2024)
The present study relates to study of role of physical development of juveniles mainly the appearance of secondary sexual characters in the age group 12 -20 years. While determining the age of juvenile in conflict with law as one of the three criteria for estimation of the age. The study covers the period of last 6 years 2007 – 2012 and has tried to evolve the physical development parameters for the mixed population of Delhi.
Keywords: Juvenile; Age estimation; Secondary sexual characters; Juvenile Justice (Care and Protection of Children) Act,3rd molar; parameters